2016
DOI: 10.3390/rs8080635
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Responses of Planted and Natural Forests to Drought Intensity in Yunnan, China

Abstract: Abstract:In recent decades, the area and proportion of planted forests have increased; thus, understanding the responses of planted and natural forests to drought are crucial because it forms the basis for forest risk assessments and management strategies. In this study, we combined the moderate-resolution imaging spectroradiometer (MODIS) enhanced vegetation index (EVI), meteorological aridity indices, and standardized precipitation evapotranspiration indices (SPEI) to identify the drought responses of plante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 68 publications
1
54
0
Order By: Relevance
“…Based on the data mentioned above, the research found that Yunnan Province, with a mean annual precipitation (MAP) of 1098.6 mm and a mean annual temperature (MAT) of 15.7 • C, is warm and humid in general. In addition, the precipitation and temperature are concentrated in summer (June-August) [10], and therefore it is a typical high-coverage region in China, where the forest cover is greater than 50.0% [39]; forests with various stock volume densities are widely distributed ( Figure 1) [40], and the best status of forests grow mainly in summer (especially in July) [10]. From 2001 to 2014, large areas of Yunnan suffered many drought events (2005)(2006)(2009)(2010)(2011)(2012)(2013)(2014) with varying intensities and duration, which significantly affected the forest ecosystem [10,41,42].…”
Section: Research Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the data mentioned above, the research found that Yunnan Province, with a mean annual precipitation (MAP) of 1098.6 mm and a mean annual temperature (MAT) of 15.7 • C, is warm and humid in general. In addition, the precipitation and temperature are concentrated in summer (June-August) [10], and therefore it is a typical high-coverage region in China, where the forest cover is greater than 50.0% [39]; forests with various stock volume densities are widely distributed ( Figure 1) [40], and the best status of forests grow mainly in summer (especially in July) [10]. From 2001 to 2014, large areas of Yunnan suffered many drought events (2005)(2006)(2009)(2010)(2011)(2012)(2013)(2014) with varying intensities and duration, which significantly affected the forest ecosystem [10,41,42].…”
Section: Research Areamentioning
confidence: 99%
“…In addition, the precipitation and temperature are concentrated in summer (June-August) [10], and therefore it is a typical high-coverage region in China, where the forest cover is greater than 50.0% [39]; forests with various stock volume densities are widely distributed ( Figure 1) [40], and the best status of forests grow mainly in summer (especially in July) [10]. From 2001 to 2014, large areas of Yunnan suffered many drought events (2005)(2006)(2009)(2010)(2011)(2012)(2013)(2014) with varying intensities and duration, which significantly affected the forest ecosystem [10,41,42]. Typical drought events in Yunnan include the mild drought of 2005 and the persistent drought in winter of 2009 to spring of 2010 [10,41].…”
Section: Research Areamentioning
confidence: 99%
See 3 more Smart Citations